(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to determine the causes of inherited land disputes regarding the Decision of the Religious Court Number 1544/Pdt.G/2020/PA.Mks and knowing legal considerations in rendering decisions by the Makassar Religious Court Judge This study uses empirical research methods. The research location was carried out in the city of Makassar, especially in the Class 1A Makassar Religious Court. Data collection techniques, library research and field research Data analysis, namely data that has been obtained, both primary and secondary data, will then be processed and analyzed to produce conclusions. The results of research on the Decision of the Makassar Religious Court Number 1544/Pdt.G/2020/PA.Mks that is, there is control over the entire inheritance of the former husband of the heir without giving it to other heirs who are also entitled to obtain the inheritance. Judges considerations in giving a decision based on the law and verses of the Qur’an relating to inheritance cases. The research recommendation is that the Class 1A Makassar Religious Court in handling inheritance cases carries out procedures in accordance with applicable regulations.